MODEL PENDIDIKAN KARAKTER DALAM MEMBANGUN KEMANDIRIAN DAN DISIPLIN SANTRI DI PONDOK PESANTREN AL- KHAIRAAT MADINATUL ILMI DOLO - Irfandi Irfandi (JP : JURNAL PENDIDIKAN, 2019)
Abstrak: The main problem of the research was how is the model of character education of students at Al-Khairaat Madinatul Ilmi Islamic Boarding School of Dolo? How were the students’ independence and discipline in building the character education at Al-Khairaat Madinatul Ilmi Islamic Boarding School of Dolo?And the objective planned to achieve, that is, to discover the developing model of character education, independence shape, and discipline shape of students at Al-Khairaat Madinatul Ilmi Islamic Boarding School of Dolo. The research was qualitative research, and the data collection was done through the observation, interview, and documentation. The data analysis was done by using inductive analysis, namely concluding based on particular facts to general ones, while the comparative one is making comparison of the data having been gained from research. The research findings show that a holistic approach was used in the students’ independence, and tadzkirah model was applied in the character education to build the students’ independence and discipline at Al-Khairaat Madinatul Ilmi Islamic Boarding School of Dolo. Few problems were experienced in developing the students, namely lack of discipline in time, especially in managing time for example in subuh pray.Key Words: model of character education, independence and discipline, Islamic Boarding School